The Evangelical Origins of the Living Constitution - JOHN W. COMPTON (Harvard University Press, 2014)
In twenty-fi rst-century America, religion seems to go hand in hand with veneration of the Constitution and its framers. Devout believers overwhelmingly endorse the view that the Constitution should be interpreted â€œas originally written.â€ Socially conservative politicians promise to oppose the nomination of judges who are not â€œdedicated to the original document and its original meaning.â€ And every year, dozens of books portraying the founders as orthodox Christian believers and the Constitution as divinely inspired appear in bookstores.1 As natural as it may seem today, however, the connection between religious faith and constitutional faith is a relatively recent development. In fact, for much of American history prominent religious activists were almost as likely to condemn the Constitution as to praise it. In 1843, for example, the abolitionist William Lloyd Garrison read the Constitutionâ€™s fugitive slave clause as evidence that the Founding generation had entered into â€œa covenant with death and an agreement with hell.â€ Carrying this belief to its logical conclusion, Garrison and other abolitionists burned copies of the Constitution in public meetings.2 And while the Garrisoniansâ€™ sensationalist methods were widely condemned, their willingness to subject the Constitution to moral criticism was far from atypical. Indeed, religiously motivated opponents of drinking, lottery gambling, and Sabbath-breaking were equally convinced that the nationâ€™s constitutional system suff ered from fl aws that threatened to undermine the moral health of the republic. In the words of New Hampshire Senator Henry Blair, a leading Gilded Age prohibitionist, the Constitution was â€œthe great legal fortress of intemperanceâ€ and â€œthe great almighty obstacle in the way of . . . reform.â€3 Signifi cantly, Blair and other nineteenth-century evangelicals did not believe, as many modern-day social conservatives do, that judges or elected offi cials had adopted a fl awed interpretation of the nationâ€™s fundamental law. Rather, like Garrison, they laid responsibility for the nationâ€™s woes directly at the feet of the Founding generation.